Evaluation of TanDEM-X 90 m Digital Elevation Model - Altunel, Arif Oguz (Informa UK Limited, 2019)
German Aerospace Center (DLR), EADS Astrium GmbH and Infoterra GmbH alliance came up with the idea of taking DTED-2 (Digital terrain elevation data, level-2) specifications to even higher standard ...
Keywords: 15. Life on land